2005
DOI: 10.1080/14017430410016422
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after emergency repair of symptomatic, unruptured abdominal aortic aneurysm: Results in 42 patients and review of the literature

Abstract: Emergency open repair of symptomatic, unruptured AAA is associated with a high risk of postoperative death. The results of this study suggest that a rather good postoperative survival rate can be expected in patients with a Glasgow Aneurysm Score <85. A watchful waiting policy or, alternatively, emergency endovascular repair should be advocated in patients with a higher score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
32
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 7 publications
4
32
0
Order By: Relevance
“…This is similar to that observed by Leo et al, 3 who reported a median GAS of 76 for survivors and 87 for those who died. Their receiver operating characteristic analysis concluded that a score of 85 was the best cutoff score to predict death.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This is similar to that observed by Leo et al, 3 who reported a median GAS of 76 for survivors and 87 for those who died. Their receiver operating characteristic analysis concluded that a score of 85 was the best cutoff score to predict death.…”
Section: Discussionsupporting
confidence: 91%
“…35,10,13,14,18 Our incidence is near the low end of the reported spectrum, similar to the 2008 report of Nevala et al 2 who reported a 6% frequency of Sx-AAA. It is unclear if these more contemporary cohorts have a lower frequency of Sx-AAAs based on increased surveillance or elective repair, or if this is related to other, unknown factors.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations